Analytic Smoothing Effect of the Time Variable for the Spatially Homogeneous Landau Equation (Journal of Partial Differential Equations, 2024)
In this work, we study the Cauchy problem of the spatially homogeneousLandau equation with hard potentials in a close-to-equilibrium framework. We provethat the solution to the Cauchy problem enjoys the analytic regularizing effect of thetime variable with an $L^2$ initial datum for positive time. So that the smoothing effect of the Cauchy problem for the spatially homogeneous Landau equation with hardpotentials is exactly same as heat equation.